Linearization approach to multi-objective quadratic set covering problem - Saxena, Ratnesh R.; Arora, S.R. (Optimization, 1998)
This paper develops an enumerative technique for solving the multi-objective set covering problem with quadratic objective functions subject to linear constraints. The objective functions and constraints are assumed to be differentiable over the feasible set. The technique is based on the linearization approach to multi-objective programming problem and cutting plane approach which then construct all the efficient p-tuple prime covers. An example to illustrate the technique is also presented.